DEVELOPMENT AND MORPHOMETRIC CHARACTERISTICS OF VETIVER GRASS UNDER DIFFERENT DOSES OF ORGANIC FERTILIZER - Holanda, Francisco Sandro Rodrigues (2021)
The use of organic fertilizers facilitates the production of plant species compared to industrial fertilizers, with a remarkable contribution to soil and water conservation through soil structuring. Vetiver grass (Chrysopogon zizanioides (L.) Roberty) is widely used in soil bioengineering projects to stabilize slopes, increasing the resistance of the soil to shear strength. The objective of this study was to evaluate the effect of the development of vetiver grass at different doses of organic fertilizer on soil stabilization. An experimental test was carried out in a greenhouse, in pots, using the following doses of organic fertilizer: T0–0 g (control); T1–135 g; T2–270 g and T3–405 g of organic fertilizer. Shoot Dry Matter (SDM), Root Dry Matter (RDM), Root Length (RL), Number of Tillers per Plant (NT) and Plant Height (PH) were evaluated. The collected data were submitted to regression analysis at 5% probability. The analysed variables showed increasing values as greater amounts of organic fertilizer, leading to an increase in soil nutrient availability and, consequently, to improved plant development.